Analisis Strategi Pengembangan Infrastruktur Asuransi Syariah Terintegrasi Di Era Digital - Mutiah, Asmaul; Nurlaila, Nurlaila; Kusmilawaty, Kusmilawaty (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the strategies required by Islamic insurance companies to enhance their infrastructure in the digital era. The primary issue identified is the inadequate development of infrastructure, which hinders the companies' ability to compete effectively in an increasingly competitive market. A qualitative approach employing the Multi-Factor Evaluation Process (MFEP) was used to evaluate and identify the most relevant strategies to address the challenges and capitalize on the opportunities presented by the digital era. The findings reveal that Islamic insurance companies require a set of integrated infrastructure development strategies. The recommended strategies include, (1) Developing differentiated products tailored to market needs, which can expand the customer base and enhance product appeal, (2) Enhancing human resource professionalism through continuous training and competency development to strengthen internal capabilities and respond to market dynamics, (3) Optimizing corporate governance by implementing advanced digital technologies to improve operational efficiency, reduce costs, and enhance service quality and (4) Intensifying product promotion efforts and increasing consumer literacy, including more aggressive education about the benefits of Islamic insurance to raise public awareness and understanding. In conclusion, the implementation of these strategies is crucial for supporting the long-term growth of Islamic insurance companies. An integrated infrastructure that is responsive to technological changes will strengthen the companies' competitive position, enabling them to be more adaptive to the evolving market needs and fully leverage the opportunities offered by the digital era. This approach will also enhance consumer trust and expand the market reach of Islamic insurance.